Residual stresses and piezoelectric properties of the HgCdTe – based compound heterostructures under the anisotropic deformation restriction - Smirnov, A. B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Narrow-gap mercury cadmium telluride thin films grown by MBE methods onto various substrates (HgCdTe/Si, HgCdTe/GaAs) were investigated as a piezoelectric heterostructure for IR detection. Mechanical stresses at the layer-substrate interface were analyzed. It was determined that for [310] oriented MCT-based structures under the anisotropic restriction of the deformation the nonzero shear components of the strain tensor arise and stress induced piezoelectric polarization is generated. Existence of the built-in electric field in the strained MCT-based heterostructure results in the spatial separation of the nonequilibrium carriers and the possibility of the room temperature detection of the IR radiation is realized.